2013
DOI: 10.1016/j.jelechem.2012.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic and steric interaction between redox polymers and some flavoenzymes in mediated bioelectrocatalysis

Abstract: H 2 O 2-generating oxidase/peroxidase (POD)-based mediated biosensors are very useful to minimize interference, but require suitable mediators which work well only for POD but not against the oxidase. Pentacyanoferrate-bound poly(1-vinylimidazole) (PVI[Fe(CN) 5 ]), PVI[Os(dcbbpy) 2 Cl] (dcbbpy = 4,4'-dicarboxy-2,2'-bipyridine) and PVI[Os(dmebpy) 2 Cl] (dmebpy = 4,4'-dimethyl-2,2'-bipyridine) have been utilized to investigate the interaction with four kinds of H 2 O 2-generating oxidases: glucose oxidase, sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The negatively charged ferricyanide does function as a mediator for AvLOx; however, it is not as effective as mPMS. Therefore, AvLOx can tolerate negative charges fairly well, although the negative charge of the ferricyanide seems to hinder the electron transfer slightly, which is in accordance with the results of Nieh et al (13) The positively charged hexaammineruthenium(III) is not utilized as an electron acceptor by AvLOx. This suggests that the access of the hexaammineruthenium(III) to the active center of AvLOx is blocked, despite the small size of the mediator.…”
Section: Electrochemical Measurements With Different Mediatorssupporting
confidence: 90%
See 3 more Smart Citations
“…The negatively charged ferricyanide does function as a mediator for AvLOx; however, it is not as effective as mPMS. Therefore, AvLOx can tolerate negative charges fairly well, although the negative charge of the ferricyanide seems to hinder the electron transfer slightly, which is in accordance with the results of Nieh et al (13) The positively charged hexaammineruthenium(III) is not utilized as an electron acceptor by AvLOx. This suggests that the access of the hexaammineruthenium(III) to the active center of AvLOx is blocked, despite the small size of the mediator.…”
Section: Electrochemical Measurements With Different Mediatorssupporting
confidence: 90%
“…(11) Finally, in 2013, Nieh et al compared metal complexes bound to polymers and concluded that the electrostatic repulsion of negative ligands and the local surface charge of the enzyme, as well as steric hindrance, lead to less efficient mediators. (13) The mediators used in this study are all small and of similar size, so steric hindrance does not explain any differences. Therefore, the most likely explanation is the electrostatic interaction of the mediators and the local surface charge of AvLOx.…”
Section: Electrochemical Measurements With Different Mediatorsmentioning
confidence: 97%
See 2 more Smart Citations
“…This fact requires them to be used in solution or immobilized on the electrode surface. A variety of freediffusing and immobilized mediators, such as ferrocene (Fc) [11] and its derivatives [12], quinone compounds [13], ferricyanide [14], transition-metal complexes [15], thionine [16], tetrathiafulvalene (TTF) [9], tetracyanoquinodimethane (TCNQ) [17], tetrathiafulvalene-tetracyanoquinodimethane complex (TTF-TCNQ) [18], phenazine methosulfate (PMS) [19,20], methylene blue (MB) and methyl viologen [13] were used to improve biosensor performance.…”
mentioning
confidence: 99%